Sharia Economy in The Sultanates of Cirebon and Mataram: Historical and Manuscript Studies - Saefullah, Asep; Burhanudin, Dede; Kholis, Nurman; Syibromalisi, Arif; Pinem, Masmedia; Rosidin, Didin Nurul; Sudrajat, Budi (AHKAM : Jurnal Ilmu Syariah, 2023)
This research focuses on the sharia economic practices during the Cirebon and Mataram Sultanates. This research uses the historical method, with four steps. These are heuristics, criticism, interpretation, and historiography.Data comes from historical artifacts, archives and manuscripts. Data was collected through library research, field observations, and FGD (FocusedGroup Discussion). The results showed that some aspects of economic practicesduring the Cirebon and Mataram sultanates in the 15 th to 17 th centuries AD were based on Islamic economic principles or sharia economics. Cirebon and Mataram’s economic policies referred to the principle of benefit, independentmanagement of land and state wealth; no foreign interference; fair land distribution to the people; just tax levies depending on people’s welfare; state revenues-based production; agriculture and plantations; as well as customsduties on goods and services. These are actually the sharia economics practices. Sharia-based economic practices are essentially forms of religious moderation practice in line with the principles of justice and equality.  Abstrak: Penelitian ini membahas praktik ekonomi syariah pada masa Kesultanan Cirebon dan Mataram melalui kajian sejarah. Penelitian ini menggunakan motode sejarah. Ada empat langkah dalam penelitian sejarah, yaitu heuristik, kritik, interpretasi, dan historiografi. Sumber data berupa benda-benda peninggalan sejarah, arsip dan manuskrip. Pengumpulan data dilakukan dengan cara kajian pustaka (library research), observasi lapangan,wawancara, dan FGD (Focus Group Discussion). Hasil penelitian menunjukkan bahwa praktik ekonomi pada masa Kesultanan Cirebon dan Mataram, khususnya abad ke-15-17 M berdasarkan pada ajaran Islam, yakni ekonomi syariah. Kebijakan Cirebon dan Mataram dalam ekonomi menganut asas kemaslahatan: pengelolaan tanah dan kekayaan negara secara mandiri, tidak ada campur tangan asing; tanah didistribusikan kepada rakyat secara adil; pungutanpajak disesuaikan dengan tingkat kesejahteraan rakyat; pendapatan negara diutamakan dari hasil bumi, pertanian dan perkebunan. Praktik ekonomi syariah hakikatnya adalah praktik moderasi beragama dalam ekonomi, denganprinsip keadilan dan kesetaraan.